PENGARUH CORPORATE GOVERNANCE TERHADAP TAX AVOIDANCE PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2011-2015 - Silvia Amalia; Aditya Septiani (Diponegoro Journal of Accounting, 2018)
The company as a taxpayer has an obligation to pay taxes to the state in accordance with the applicable laws and regulations. The tax paid is important for the state as a source of state revenue to function as a driver of the country's economic growth and development, while for the company will be a reduction in corporate profits. Tax avoidance can be done legally by the management by observing existing tax regulations and then looking for weaknesses of the regulation to be used as tax evasion. The implementation of corporate governance in companies is important because it helps internal and external parties of the company to see whether the company follows the principles of good corporate governance, and also helps the government to see violations committed by the company in the company's financial statements.Based on agency theory, the concept of corporate governance is an agency conflict control effort, where corporate governance regulates and overcomes management behavior that prioritizes personal interests so that there can be harmony between the interests of shareholders and managers.The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2011-2015. The sampling method used is the probability method with the sampling technique using judgment sampling method. The number of companies that were sampled were 32 companies. Data taken from the company's annual report were analyzed using multiple regression analysis.The results of this study indicate that independent commissioners, audit committees, have a positive effect on tax avoidance, while institutional ownership, board of commissioners, and audit quality have a negative and significant effect on tax avoidance. Implications in this study are expected to provide information for users of related financial statements in policy making to help increase company value and improve, evaluate and improve management performance in the future.